Students’ Mastery of Adjective Clause: A Case Study towards the Second Semester Students of English Department (Universitas Pamulang, 2020)
This is a case study that aims at analyzing the students’ ability in answering grammar questions about adjective clauses. The method used to analyze the data is qualitative descriptive method. The result of the study showed how well students’ ability of the second semester student of English Literature department at Universitas Pamulang in dealing with grammar questions about adjective clauses. There were 26 random students from two different classes in the same semester who were included in this study. The study shows that the average of students score resulted them to be classifed to have Fair (got 60 to 69 score) category of adjective clause mastery by reaching 46% of the total percentage.